Burkina Faso : Perceived Shocks, Vulnerability, Food Insecurity, and Poverty - World Bank (Washington, DC, 2013)
Burkina Faso's Poverty Reduction Strategies (PRS) of the 2000s, which were implemented as annually rolled-over Priority Action Programs, focused on four pillars: a) accelerating broad based growth; b) expanding access to social services for the poor; c) increasing employment and income-generating activities for the poor; and d) promoting good governance. Increased public expenditure and targeted social service provision also led to improved access to basic services. In the area of education, progress has been made in terms of school infrastructure. Over the period of 2003-2008, substantial expansion (around 40 percent) of both the number of schools and the number of classrooms was achieved. Controlling and treating epidemic diseases also had good results, thanks to prevention and public awareness efforts and improved hygiene. Meanwhile, the country has been through several exogenous shocks and crises likely to have affected the pattern of poverty outcomes. In the past two decades, Burkina Faso's income per capita growth has been positive and less volatile relative to the past. Recent growth trends appear to be anchored by a general recovery in the primary sector. Household consumption was just as volatile as income per capita in the 1980s, but recovered substantially after the country gained competitiveness in the latter half of the 1990s following devaluation. However, since then, consumption has exhibited much more volatility than output. Finally, most the social indicators show an improvement in Burkina Faso since the early 1980s. Burkina Faso has kept pace with the overall positive trends observed in Sub-Saharan Africa and low income countries.